PANCASILA SEBAGAI LANDASAN ILMU DALAM PENGEMBANGAN TEKNOLOGI INFORMASI YANG BERETIKA - Sembodo, M.Ubay Arashy Supo (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The purpose of this research is to perceive the position of marital assets in mixed marriages in terms of the provisions of the Marriage Law NO.16 of 2019, and what are the provisions for marital assets of a foreign citizen who had married in Indonesia with an Indonesian citizen. The results of this study show that property acquired during marriage becomes joint property, but the law does not distinguish what types of property can qualify as joint property. Provisions for assets in mixed marriages of different nationalities, namely between a foreign citizen and an Indonesian citizen, the arrangement is according to the law which is valid in Indonesia. Likewise with regard to joint property acquired by husband and wife in marriages of different nationalities, property that can be owned by foreign nationals is movable property, while fixed objects, such as land and those which are equated with land cannot be owned by them.